Clinching in In Situ CT—A Novel Validation Method for Mechanical Joining Processes - Köhler, Daniel; Kupfer, Robert; Troschitz, Juliane; Gude, Maik (The Minerals, Metals & Materials Series)
Force–displacement measurements and micrograph analyses are commonly used methods to validate numerical models of clinching processes. However, these methods often lead to resetting of elastic deformations and crack- closing after unloading. In contrast, the in situ computed tomography (CT) can provide three-dimensional images of the clinch point under loading conditions. In this paper, the potential of the in situ investigation of a clinching process as validation method is analyzed. For the in situ testing, a tailored test set-up featuring a beryllium cylinder for load-bearing and clinching tools made from ultra-high-strength titanium and Si3N4 are used. In the experiments, the clinching of two aluminum sheets is interrupted at specific process steps in order to perform the CT scans. It is shown that in situ CT visualizes the inner geometry of the joint at high precision and that this method is suitable to validate numerical models.
Keywords: Clinching; Non-destructive testing; Computed tomography; In situ CT

Debugging Static Analysis - Nguyen Quang Do, Lisa; Krüger, Stefan; Hill, Patrick; Ali, Karim; Bodden, Eric (IEEE Transactions on Software Engineering)
Keywords: Debugging; Static analysis; Tools; Computer bugs; Standards; Writing; Encoding; Testing and Debugging; Program analysis; Development tools; Integrated environments; Graphical environments; Usability testing

Mathematics-related Competence of Early Childhood Teachers Visiting a Continuous Professional Development Course: An Intervention Study - Bruns, Julia; Eichen, Lars; Gasteiger, Hedwig (Mathematics Teacher Education and Development (MTED))
Recent studies highlight early childhood teachers’ mathematics-related competence. Developing this competence should be a main aspect of early childhood teachers’ education. This is, however, not the case in all countries. Consequently, high-quality professional development courses are needed. Based on research results, we developed a competence-oriented continuous professional development course ("EmMa") and examined the effects of "EmMa" by asking: How does "EmMa" affect the development of early childhood teachers’ i) mathematical content knowledge, ii) mathematical pedagogical content knowledge and iii) beliefs towards mathematics in general? To answer these questions, we conducted a pre-test/post-test study including a control group with 99 in-service early childhood teachers. Results show that the course affected teachers’ mathematical pedagogical content knowledge and static orientation towards mathematics positively. From this we conclude that scaling-up "EmMa" might be a suitable approach to bridge the gap between pre-service education with nearly no mathematics and the challenges of early mathematics education.
Keywords: Beliefs; Competency Based Teacher Education; Control Groups; Early Childhood Education; Faculty Development; Foreign Countries; Inservice Teacher Education; Intervention; Mathematical Aptitude; Mathematics Skills; Pedagogical Content Knowledge; Preschool Teachers; Pretests Posttests; Professional Continuing Education; Statistical Analysis; Teacher Competency Testing

Time-efficient dynamic analysis of structures exhibiting nonlinear peak bending - Sprock, Christian; Sextro, Walter (Instrumentation and Measurement Technology Conference (I2MTC) Proceedings, 2014 IEEE International)
A measurement method is presented that combines the advantages of the multisine measurement technique with a prediction method for peak bending behavior. This combination allows the analysis of the dynamic behavior of mechanical structures at distinctly reduced measurement durations and has the advantage of reducing high excitation impacts on the structure under test.
Keywords: bending; dynamic testing; measurement; structural engineering; vibrations; measurement durations; mechanical structures; multisine measurement technique; nonlinear peak bending behavior; prediction method; time-efficient dynamic analysis; Heuristic algorithms; Nonlinear systems; Oscillators; Time measurement; Time-frequency analysis; Vibrations

A Systematic Approach to Combined HW/SW System Test - Krupp, Alexander; Müller, Wolfgang (Proceedings of DATE’10)
Today we can identify a big gap between requirement specification and the generation of test environments. This article extends the Classification Tree Method for Embedded Systems (CTM/ES) to fill this gap by new concepts for the precise specification of stimuli for operational ranges of continuous control systems. It introduces novel means for continuous acceptance criteria definition and for functional coverage definition.
Keywords: System testing; Automatic testing; Object oriented modeling; Classification tree analysis; Automotive engineering; Mathematical model; Embedded system; Control systems; Electronic equipment testing; Software testing

Rupeas: Ruby Powered Event Analysis DSL - Woehrle, Matthias; Plessl, Christian; Thiele, Lothar
Wireless Sensor Networks (WSNs) are unique embedded computation systems for distributed sensing of a dispersed phenomenon. While being a strongly concurrent distributed system, its embedded aspects with severe resource limitations and the wireless communication requires a fusion of technologies and methodologies from very different fields. As WSNs are deployed in remote locations for long-term unattended operation, assurance of correct functioning of the system is of prime concern. Thus, the design and development of WSNs requires specialized tools to allow for testing and debugging the system. To this end, we present a framework for analyzing and checking WSNs based on collected events during system operation. It allows for abstracting from the event trace by means of behavioral queries and uses assertions for checking the accordance of an execution to its specification. The framework is independent from WSN test platforms, applications and logging semantics and thus generally applicable for analyzing event logs of WSN test executions.
Keywords: Rupeas; DSL; WSN; testing

EvAnT: Analysis and Checking of event traces for Wireless Sensor Networks - Woehrle, Matthias; Plessl, Christian; Lim, Roman; Beutel, Jan; Thiele, Lothar (IEEE Int. Conf. on Sensor Networks, Ubiquitous, and Trustworthy Computing (SUTC))
Keywords: WSN; testing; verification

Increasing the Reliability of Wireless Sensor Networks with a Distributed Testing Framework - Woehrle, Matthias; Plessl, Christian; Beutel, Jan; Thiele, Lothar (Proc. Workshop on Embedded Networked Sensors (EmNets))
Keywords: WSN; testing; distributed; embedded

Automated Wireless Sensor Network Testing - Beutel, Jan; Dyer, Matthias; Lim, Roman; Plessl, Christian; Woehrle, Matthias; Yuecel, Mustafa; Thiele, Lothar (Proc. Int. Conf. Networked Sensing Systems (INSS))
Keywords: WSN; testing; verification

Classification Trees for Functional Coverage and Random Test Generation - Krupp, Alexander; Müller, Wolfgang (Proceedings of the Design Automation & Test in Europe Conference)
This article presents the classification tree method for functional verification to close the gap from the specification of a test plan to SystemVerilog (Chandra and Chakrabarty, 2001) test bench generation. Our method supports the systematic development of test configurations and is based on the classification tree method for embedded systems (CTM/ES) (Chakrabarty et al., 2000) extending CTM/ES for random test generation as well as for functional coverage and property specification
Keywords: Classification tree analysis; System testing; Embedded system; Safety; Automatic testing; Automation